Influence of Race, Ethnicity and Social Determinants of Health on Diabetes Outcomes - Walker, Rebekah J; Strom Williams, Joni; Egede, Leonard E (The American journal of the medical sciences, 2016)
There is strong evidence that race, ethnicity and social determinants of health significantly influence outcomes for patients with diabetes. A better understanding of the mechanisms of these relationships or associations would improve development of cost-effective, culturally tailored programs for patients with diabetes. This article reviews the current state of the literature on the influence of race and ethnicity and social determinants of health on process of care, quality of care and outcomes for diabetes, with particular emphasis on the rural South to give an overview of the state of the literature. The literature review shows that racial or ethnic differences in the clinical outcomes for diabetes, including glycemic, blood pressure (BP) and lipid control, continue to persist. In addition, the literature review shows that the role of social determinants of health on outcomes, and the possible role these determinants play in disparities have largely been ignored. Psychosocial factors, such as self-efficacy, depression, social support and perceived stress, show consistent associations with self-care, quality of life and glycemic control. Neighborhood factors, such as food insecurity, social cohesion and neighborhood esthetics have been associated with glycemic control. Perceived discrimination has also been associated with self-care and the psychological component of quality of life. Healthcare professionals need to be skilled in assessing social determinants of health and taking them into consideration in clinical care. In addition, more research is needed to identify the separate and combined influence of race and ethnicity and social determinants of health on process of care, quality of care and outcomes in diabetes, especially in the South, where the burden of disease is particularly high.